Volatility Spillover amongst BSE w.r.t those of India’s top Trading Partners - Shivam Arora, Anish Agarwal (International Journal of Advanced Science and Technology, 2020)
Aim and Objective: With this research paper we aim to examine the spillover effects between the financial markets of USA, China, Hong Kong, Singapore and UK (top trading partners of India) w.r.t India.Methods Used- Weekly data has been considered from January 1 2010 to January 1 2020, consisting of 5 trading days a week. The stationarity was checked using ADF and PP unit root tests while the volatility spillover effects were analysed using BEKK GARCH modelResults-After examining the volatility spillover effects between India and the previously mentioned countries we observe there is transmission of both shock and price volatility from India to other countries as well as a transmission of shock volatility from China’s market to India’s market.